THE INFLUENCE OF WORKING MOTHERS' PARENTING PATTERNS ON EARLY CHILDHOOD INDEPENDENCE - Zakiatul A'la; Ari Sofia; Vivi Irzalinda (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2023)
In the current era of globalization, the demands for needs in family life are increasing, thus making mothers play a dual role in the household. This will indirectly affect the care of working mothers towards early childhood independence. This research was aimed to know the effect of working mother’s parenting on independence of children aged 5 to 6 years old. This research used a quantitative research type with survey method. Research sample was taken with used purposive sampling namely a working mother out of home and a mother who have children aged 5 to 6 years old many as 57 respondents. The data collection tools used are questionnaire on parenting of working mother’s and self-reliance questionnaire for children aged 5-6 years old. Data analysis in this research used a simple linier regression test. The result of this research showed that there is an influence between the parenting of working mother’s amd the independence of children aged 5-6 years old with the value of F count is 13.968 and the contribution of the positive influence is 20.3 percent. Suggestions for government policies and structured parenting programs to improve early childhood independence in working mothers' families. Kata Kunci: pola asuh, kemadirian, ibu bekerja, anak usia dini.